2001
DOI: 10.1046/j.1525-142x.2001.003002059.x
|View full text |Cite
|
Sign up to set email alerts
|

Modularity, evolvability, and adaptive radiations: a comparison of the hemi‐ and holometabolous insects

Abstract: Despite recent attention given to the concept of modularity and its potential contribution to the evolvability of organisms, there has been little mention of how such a contribution may affect rates of diversification or how this would be assessed. A first key prediction is that lineages with relatively greater degrees of modularity in given traits should exhibit higher rates of diversification. Four general conditions for testing this prediction of the modular evolvability hypothesis are outlined here. The po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
140
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(143 citation statements)
references
References 60 publications
3
140
0
Order By: Relevance
“…These facts, long casually observed, have suggested that key evolutionary changes have been responsible for generating much of the richness in this very diverse group, and four such evolutionary innovations have held centre stage [18,19]: the insect bauplan [35], wings [36], wing folding [21] and complete metamorphosis [23]. Here, we have reported evidence that both fossil family rspb.royalsocietypublishing.org Proc.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…These facts, long casually observed, have suggested that key evolutionary changes have been responsible for generating much of the richness in this very diverse group, and four such evolutionary innovations have held centre stage [18,19]: the insect bauplan [35], wings [36], wing folding [21] and complete metamorphosis [23]. Here, we have reported evidence that both fossil family rspb.royalsocietypublishing.org Proc.…”
Section: Discussionmentioning
confidence: 68%
“…[11]). Fossil studies have been rare, but Yang [23] used Lyellian survival analysis on family-level data [24] to suggest that extinction rates do not differ between Holometabola and Paraneoptera, and hence that differences in origination rates probably account for the larger increase in families in Holometabola. However, Yang only considered this single key innovation, and the dataset on which his study was based is now considerably dated.…”
Section: Introductionmentioning
confidence: 99%
“…The evolution of higher facial colour complexity within genera indicates de-coupling of the phenotype of different facial regions, which is consistent with the idea that these might constitute variational modules 10 . Modularity of the primate face is a likely advantage of these more structured facial colour patterns because it can enable higher levels of interspecific diversity 10,36,37 that would in turn be beneficial for species recognition. A modular framework characterizes the cranial morphology of many mammals, including primates [38][39][40] ; however, facial colour patterns have not been investigated in the context of modularity even though research suggests that various aspects of this system might be modular.…”
Section: Discussionmentioning
confidence: 99%
“…But their permanent establishment would have been assured only after the emptying of ecological space after the end-Permian event. It is this profound, postPermian ecological transformation that provided a sufficient number of available niches that allowed permanent establishment of several major clades with complete metamorphosis (Yang, 2001;Mayhew, 2002Mayhew, , 2007. This suggests that holometaboly was initially important in species-byspecies replacement of nonholometabolous taxa resulting from Permian climatic vicissitude that only later was implemented during the Triassic when a different process of niche reorganization allowed occupation.…”
Section: Importance Of the Larval Stage For Early Holometabolan Taxonmentioning
confidence: 99%